ISLAMIC EDUCATION CURRICULUM BASED ON THE QURAN: ALIGNING EDUCATION WITH SOCIETAL NEEDS - Maulana, Irsyad (IHTIROM : Jurnal Manajemen Pendidikan Islam, 2024)
The Qur'an is the primary source of teachings for Muslims and the principal guide in everyday life, including Islamic education. Changing societal needs are a key factor in developing Islamic education curricula to ensure that school graduates meet contemporary demands. This research aims to develop a Qur'an-based Islamic education curriculum to produce graduates who understand religious teachings and can benefit society. It acknowledges that curriculum development is the responsibility of stakeholders and educators in educational institutions. Based on this premise, the researcher writes this literature to provide information for developing Quran-based Islamic Education curricula that meet societal needs. This study is a literature review employing qualitative descriptive methodology with a pragmatic approach. Primary data are derived from the Qur'an, while secondary data come from books and journals. Data collection techniques include documentation, encompassing literature such as the Qur'an, journal articles, and online sources. Data analysis follows the Miles and Huberman method, involving data collection, presentation, reduction, and verification to draw accurate conclusions. The research findings underscore the importance of aligning Islamic education curricula with societal needs. Varied implementation in madrasahs requires effective management, adequate resources, and collaboration among principals, teachers, and educational staff. Continuous evaluation is crucial to maintaining the relevance and effectiveness of the curriculum. In conclusion, this research emphasizes that a Qur'an-based Islamic education curriculum should be tailored to meet societal needs. Varied implementation necessitates effective management, adequate resources, and collaboration among madrasah principals, teachers, and educational staff to achieve quality education goals.